Juridical Review of the Crime of Inducing Obscenity Against Children (Case Study in Polres, Bombana Regency) - L, ST Fatmawati; BT. Tolo, Suriani; Hijriani, Hijriani; Marlin, Marlin; Dewi, Ayu Lestari; Ula, Hamdil (International Journal of Management and Education in Human Development, 2023)
Indonesia is a country that was formed based on law and has been used by society in everyday life. So that every movement or action of society has legal values in it. However, as time goes by, the types of acts that violate the law are increasingly diverse in society. The government and the authorities have repeatedly provided outreach to make the public aware of the consequences of a criminal act that they commit, not only harming other people but themselves, but in its development this effort has not been enough to make the public aware. To obtain the data and information needed for the preparation of this thesis, the research will be carried out at the Bombana District Police Headquarters. This place was chosen because the author felt that research data on the crime of persuading children could be obtained at the Bombana Regency Police Station. The application of material criminal law by the Panel of Judges applying Article 81 Paragraph (2) of Law Number 35 of 2014 concerning Child Protection and Article 82 of Law No. 35 of 2014 concerning Child Protection because the victims are children and the basis for its implementation is the lex specialist principle. The legal considerations of the panel of judges in imposing criminal sanctions on the defendant were not appropriate because the sentence imposed on the defendant still contained deficiencies that were not by his actions so that it could damage the child mentally and sociologically. It is hoped that judges will be clearer in considering aggravating and mitigating factors for the defendant, this is related to the value of fairness of a decision for all parties and the deterrent effect of the decision. It is hoped that parents will pay more attention and understanding to their children so that children do not get trapped, let alone become victims of criminal acts of sexual abuse that destroy the child's future. An approach from a religious perspective is very necessary because that way people can control their desires so as not to commit wrong actions because this is based on religious values.